Global Military & International Regulation: Legal Dynamics In Strategic Alliances - Arief Fahmi Lubis (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This article examines the legal dynamics of international law in the formation and implementation of strategic military alliances in the era of globalized security. The increasing expansion of defense cooperation among states reflects a shift from traditional security paradigms toward collective and cooperative security models. Nevertheless, military alliances remain subject to the framework of international law, particularly the provisions of the United Nations Charter, the principles of sovereignty, the prohibition on the use of force, and international humanitarian law. This research employs a normative juridical method with statutory, conceptual, and case-based approaches. The findings indicate that legal dynamics within strategic alliances are characterized by tension between military operational effectiveness and normative legal constraints, particularly regarding accountability, jurisdiction, and state responsibility. Therefore, harmonization between domestic regulations and international obligations, as well as strengthened accountability mechanisms in collective military operations, are essential to maintaining legitimacy and global security stability